Is Malaysia Little Brother of Indonesia? A Framing Analysis of Ambalat Conflict - Dunan, Amri; Adnan, Hamedi Mohd (SOSIOHUMANIKA, 2014)
ABSTRACT: Reformation era in Indonesia, since 1998, became the new act for relationship between Indonesia and Malaysia. Currently, some break up started after certain incidents happened and influence the intimate relationship between these two countries. For those incident happened, the case of Ambalat Block were reported widely by the media and being the hottest topics for discussion. This article describes and analyzes the framing of Malaysia verbally and non-verbally in the news of âMetro TVâ and âTV Oneâ from Indonesia television in Ambalat conflict. This research uses framing analysis âTelevision Newsâ model developed by Amri Dunan & Hamedi Mohd Adnan (2013); and the inductive qualitative analysis with matrix method developed by B. Van Gorp (2010). In the cases of Ambalat framed by âMetro TVâ and âTV Oneâ try to place Malaysia in the situation of âlittle brotherâ with the means of didnât appreciate the sibling relationship and forgot the origin. Thus, Malaysia was framed negative in the news reporting of âMetro TVâ and âTV Oneâ. However, the most interested thing is the reporter from âMetro TVâ and âTV Oneâ in Jakarta (Indonesia) tried to present the news reporting which fulfill the standard of journalistic. But, the reality is the value of patriotic and nationalism in their heart has made the news reporting shows the partiality to Indonesia. In future, the other programs like Talk Show or the sports program, which involved the relationship Indonesia-Malaysia, should put some attention for research. KEY WORD: Indonesia-Malaysia conflict, framing, television news, âMetro TVâ and âTV Oneâ, political ideology, and visual reporting.Â RESUME: âIakah Malaysia Adik daripada Indonesia? Satu Analisis Bingkai Konflik Ambalatâ. Era Reformasi di Indonesia, sejak tahun 1998, menjadi amalan baru dalam hubungan Indonesia dan Malaysia. Pada masa ini, beberapa perpecahan bermula selepas insiden tertentu yang berlaku dan memberi kesan dalam hubungan intim antara kedua-dua negara. Bersabit insiden yang berlaku, kes Blok Ambalat dilaporkan secara meluas oleh media dan menjadi topik hangat dalam perbincangan. Artikel ini menerangkan dan menganalisis bingkai Malaysia secara lisan dan bukan lisan dari televisyen Indonesia, iaitu dalam berita-berita âMetro TVâ dan âTV Oneâ, bercanggah masalah Ambalat. Kajian ini menggunakan analisis bingkai model âBerita Televisyenâ yang dibangunkan oleh Amri Dunan & Hamedi Mohd Adnan (2013); dan analisis kualitatif induktif dengan kaedah matriks yang dibangunkan oleh B. Van Gorp (2010). Dalam kes-kes Ambalat yang dibingkai oleh âMetro TVâ dan âTV Oneâ cuba untuk meletakkan Malaysia didalam keadaan selaku âadik lelakiâ dengan cara-cara yang tidak menghargai hubungan adik-beradik dan terlupa asal-usul. Oleh itu, Malaysia telah dibingkai negatif dalam laporan berita daripada âMetro TVâ dan âTV Oneâ. Walau bagaimanapun, perkara yang paling penting adalah bahawa wartawan daripada âMetro TVâ dan âTV Oneâ di Jakarta (Indonesia) cuba mengemukakan laporan berita yang memenuhi standard kewartawanan. Tetapi, hakikat daripada nilai-nilai patriotik dan nasionalisme dalam hati mereka telah membuat laporan berita yang menunjukkan sikap menyebelahi kepada Indonesia. Pada masa hadapan, program-program lain seperti âTalk Showâ atau program sukan, yang membabitkan hubungan baik antara Indonesia-Malaysia, perlu diambil berat dan pemerhatian untuk penyelidikan.KATA KUNCI: Konflik Indonesia-Malaysia, bingkai, berita televisyen, âMetro TVâ dan âTV Oneâ, ideologi politik, dan laporan visual.Â Â About the Authors: Amri Dunan and Hamedi Mohd Adnan are the Lecturers at the Department of Media Studies, Faculty of Art and Social Sciences UM (University of Malaya), Pantai Dalam Street, 50603 Kuala Lumpur, Malaysia. Corresponding authors are: amri_dunan@yahoo.co.id and hamedi@um.edu.myHow to cite this article? Dunan, Amri & Hamedi Mohd Adnan. (2014). âIs Malaysia Little Brother of Indonesia? A Framing Analysis of Ambalat Conflictâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7, No.1 [Mei], pp.1-8. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of article: Accepted (March 11, 2014); Revised (April 15, 2014); and Published (May 20, 2014). Â  Â